(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India’s healthcare system continues to face significant challenges, including low public funding, inadequate infrastructure, and limited access to high-quality services for underserved populations. Non-governmental organizations (NGOs) have become vital partners in addressing these gaps by complementing government initiatives with innovative, community-based health solutions. This study explores the roles and impacts of NGOs in improving public health in India, focusing on their diverse contributions to preventive care, maternal and child health, nutrition, communicable and non-communicable diseases, and cancer care. Case studies of prominent NGOs—such as Doctors for You, Rural Health Care Foundation, Swasth Foundation, Foundation for Mother and Child Health, CanKids Kidscan, Swasthya Swaraj, Aarogya Seva, MAYA, SEARCH, and Arogya Mandal—illustrate their unique approaches, which range from palliative cancer support and tribal health empowerment to disaster relief and affordable primary care. The report highlights how NGOs not only provide essential healthcare services but also empower communities, reduce out-of-pocket expenses, and drive systemic change. Due to their flexibility and grassroots engagement, especially in underserved rural and tribal areas, NGOs play a crucial role in addressing healthcare inequities. To create a more inclusive, sustainable, and equitable public health ecosystem in India, it is imperative to strengthen collaborations among the government, NGOs, and local communities. Reason: The revision improves clarity, flow, and readability by restructuring sentences and enhancing vocabulary. It corrects punctuation and spacing errors, such as adding a missing space after a period. Technical accuracy is improved by specifying